Collegiate athletic trainers' experiences planning for return-to-sports during COVID-19: A qualitative research study - Post, E. G.; di Santi, J. S.; Eason, C. M.; Root, H. J.; Abdenour, T. E. (The Internet Journal of Allied Health Sciences & Practice, 2021)
Purpose: The purpose of this study was to explore the role of intercollegiate head athletic trainers in the process of planning to resume sport, as well as their experiences across the course of the pandemic to identify key strategies, challenges, and future considerations during the Covid-19 pandemic. Method: This exploratory, descriptive qualitative study was conducted via one-on-one semi structured interviews through the Zoom video conference technology. Twenty-four head athletic trainers across NCAA Division I, II, and III institutions participated in the study. Results: Emerging themes included the development of detailed, institution-specific plans with shared elements such as policies for testing and screening, modifications to facilities and cleaning, and incorporation of coach and athlete education. Athletic trainers discussed the processes they used to create their return-to-sport policies, which included professional development and interprofessional collaborations. While participants were confident in their plans, they acknowledged the need to overcome logistical and psychosocial challenges, such as the recognition that the success of their plans relied on numerous variables that could not be completely controlled. Conclusion: It is clear that NCAA ATs have played - and will continue to play - an integral role in overcoming challenges to promote a safe return-to-sports amidst the COVID-19 pandemic via education, policy making, and delivery of healthcare services. The challenges imposed by the accompanying set of circumstances have strained these ATs` practical tendencies and procedures. ATs have met these challenges through collaboration, information-seeking, and acceptance of the situation. NCAA ATs have embraced the opportunity to lead the way towards safe, successful campus reopening and resumption of competition.